حجاجية الحديث النّبوي الشريف في صحيح البخاري نماذج مختارة - ذهب دنيا; سبوعي مروة (University of El-Oued جامعة الوادي, 2025)
الملخص: الخطابة فن نثري يُخاطب به الجمهور وتعمل على الإقناع والإستمالة، وتمتاز بالإيجاز والإرتجال والترتيب والحجاج، هذا الأخير الذي اختلفت مفاهيمه من جدل ومُناظرة وحوار، فهو يُعد أساسا من عمليات التواصل؛ إذ يَقوم على تَقديم الحُجَج المُـؤدّية إلى نتيجة مُعـينة مع وُجوب حضور الطرفين المُحَاجِج والمَحجوج. إنّ الخطاب النبوي خطاب حجاجي بالدرجة الأولى، وهذا مالاحضناه عند تحليلنا للأَحاديث النبويّة، إذ تعددت فيها آليات الحجاج من عوامل وروابط حِجَاجِيَّة التي تقوم بربط الحُجج بعضها ببعض لتدعيم النتيجة. كما تعدّدت آليات التوجيه في الحديث النبوي بين الأمر والنهي والشرط، ومااشتَمَلت عليه هذه الصّيغ من معانٍ أصلية وقدرتها على الإقناع، كَمَا احتلّت آليات الحجاج البلاغيّة دور كبير في الحديث النبوي، كـتوظيف الإستعارة والكناية والسجع والمقابلة..... هذا كله جعل من الخطاب النبوي خطابا حجاجيا، يعمل على إستمالة المحجوج وإقناعه بالقضية المطروحة. Synopsis: Oratory is a prose art that addresses the audience and works to persuade and attract, and is characterized by brevity, improvisation, arrangement and pilgrims, the latter, whose concepts have differed from debate, debate and dialogue, it is considered the basis of communication processes; it is based on presenting arguments leading to a certain result with the need for both parties to the arguments and arguments. The prophetic discourse is primarily a pilgrim discourse, and this is what we noticed when we analyzed the prophetic hadiths, as there are many Pilgrim mechanisms from factors and Pilgrim links that link the arguments to each other to support the result. There are also a variety of guidance mechanisms in the Hadith between the command, the Prohibition and the condition, and what these formulas contained of original meanings and their ability to persuade, and the rhetorical mechanisms of pilgrims played a major role in the Hadith, such as the use of metaphor, metonymy, assonance and interview..... All this has made the prophetic speech a Hajj speech, which works to woo the pilgrim and convince him of the issue at hand.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: الجدل• المناظرة•آليات الحجاج البلاغيّة واللّغوية• السّلم الحجاجي• العوامل والروابط الحجاجية• الإقناع• التأثير•البرهنة• القصد• الإستدلال•الحجّة• التّناغُم; debate * rhetorical and linguistic Pilgrim mechanisms• Pilgrim ladder• factors and Pilgrim links• persuasion• influence•proof• intent• inference•argument• harmony•